Planning Analysis of the Utilization of Ocean Currents as a Power Plant Using Gorlov Turbines in the Botang Lomang District, South Halmahera Regency - Idham A Djufri (Universitas Khairun, 2023)
Electrical energy is a basic need of the community and supports aspects of national life and development, including improving living standards. Indonesia actually has the potential for new renewable energy sources in large quantities. Ocean current energy is one of the renewable energy whose existence is continuous and environmentally friendly. One of the potential energy of ocean currents is in the Botang Lomang District Area. This study aims to determine the amount of power generated from the potential of ocean currents. The minimum average speed at a depth of 10 meters is (0.21 m/s) and the maximum is (1.26 m/s). And the minimum average speed at a depth of 20 meters is (0.28 m/s) and maximum (1.67 m/s). The power obtained from the minimum and maximum ocean current speeds at a depth of 10 meters is 252 Watts to 54.654 kW. While the power obtained from the minimum and maximum sea current speeds at a depth of 20 meters is 599 Watts to 127,252 kW.